Evaluation of Graphical Weather Product Interpretation: Implications for Overlaying Weather Product Design. (September 2018) - DeFilippis, Nicholas; King, Jayde; Guinn, Thomas; Ortiz, Yolanda; Berendschot, Quirijn; Cole, Amber; Blickensderfer, Beth
The majority of Aviation Weather-related accidents occur in the General Aviation (GA) community. In order to improve pilot safety, the FAA and Aviation Weather Center are working towards developing tools which have an improved level of effectiveness. Unfortunately, shortcomings in the interpretability of these tools can lead to further dangerous situations. The new Graphical Forecast for Aviation (GFA) tool is an unfortunate example. The GFA is composed of three previously existing weather displays: Radar, Satellite, and Station Plots. This study assessed and compared pilots' interpretation of the three displays to assess interpretability. Certified pilots (n = 283) completed a set of weather product interpretation questions. Between and within groups analyses were run to determine the effect of Certificate and/or Rating on product score. Results indicated that pilots have a low-performance in the interpretation of Radar, Satellite and Station Plot products and, in turn, will likely score low with the GFA. Training and usability improvements are also discussed.